Rebels with a cause. Aldo van Eyck and Pancho Guedes, how to find a meaning for the act of built - Tostoes, Ana (CEAA/ESAP-CESAP, 2019)
This paper aims to look at an uncommonly critical attitude against the bureaucratic functionalism in force within a kind of International Style, developing an authentically modern and human architecture in the scope of the Team 10’s battle. Considering Aldo van Eyck (1918-1999) and Pancho Guedes’ (1925-2015) works and thoughts, their parallel paths, sometimes crossed, are analysed: they were both part of Team 10 and they both defined architecture as the “built meaning”, recalling its multiple meanings, languages and responsibilities: ‘I claim for architects the rights and liberties that painters and poets have held for so long’. Aldo van Eyck, from the studies on the sub-Saharan Dogon region to the PREVI proposals in Peru, and Pancho Guedes, from the survey on the Mapogga doors to his surrealist approaches in Mozambique, give examples of the transformation process, on how the modern project got elasticity, creativity, endurance, and finally feeding the utopia. The argument addresses the fact that these two minds envisaged architecture as a language with an emotional impact and a social and cultural scope. Bearing in mind architecture as the primary visual medium with which human society expresses and reveals itself, architecture is conceived as a dialogue and the design of buildings as means for creating relations between people rather than as an end in itself.
Keywords: Team 10; Aldo van Eyck; Pancho Guedes; modern project; architecture language